Validations of the international classification for nursing practice: integrative review (Research, Society and Development, 2022)
Objective: To identify characteristics of studies that validated concepts of the International Classification for Nursing Practice. Method: Integrative review with articles published between 1996 and 2021, in PubMed, VHL, CINAHL, SCOPUS, Web of Science and SciELO. Included articles in Portuguese, English or Spanish that validated diagnoses, results or nursing interventions. Literature reviews, previous notes and editorials are excluded. Characteristics related to the validated concept, validation typology, scale and technique, type and selection of the study population were collected. Presentation of results organized by the PRISMA guideline. Results: Sample of 27 articles. The validation of concepts related to dignified death, care for postpartum women and pediatrics stood out. Content and clinical validation predominated; 41% of the surveys used the agreement index and 26% the content validation index. Experts participated in 96% of the validations. Conclusions: Likert scale, expert assessment and agreement index are strategies adopted in validation research. For the selection of specialists, the criteria are modified and clinical experience is the most used, non-standardized criterion.